2014
DOI: 10.1186/s12866-014-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Cecropin P1 inhibits porcine reproductive and respiratory syndrome virus by blocking attachment

Abstract: BackgroundPorcine reproductive and respiratory syndrome virus (PRRSV) is a continuous threat to the pig industry, causing high economic losses worldwide. Current vaccines have specific limitations in terms of their safety and efficacy, so the development of novel antiviral drugs is urgently required. The aim of this study was to evaluate the inhibitory effects and underlying molecular mechanisms of the antimicrobial peptide cecropin P1 (CP1) against PRRSV infection in vitro.ResultsCP1 not only displayed extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Cecropin P1 also shows a significant inhibitory effect on human fungal pathogen C. albicans [ 74 ]. Cecropin P1 inhibits PRRSV by blocking attachment [ 75 ]. Cecropin P1 inhibits viral particle release and attenuates virus-induced apoptosis [ 75 ].…”
Section: Insect Antimicrobial Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cecropin P1 also shows a significant inhibitory effect on human fungal pathogen C. albicans [ 74 ]. Cecropin P1 inhibits PRRSV by blocking attachment [ 75 ]. Cecropin P1 inhibits viral particle release and attenuates virus-induced apoptosis [ 75 ].…”
Section: Insect Antimicrobial Peptidesmentioning
confidence: 99%
“…Cecropin P1 inhibits PRRSV by blocking attachment [ 75 ]. Cecropin P1 inhibits viral particle release and attenuates virus-induced apoptosis [ 75 ]. Currently, biosensors using cecropin P1 have been developed, and the peptide has been immobilized through different termini results in different functions and activities [ 76 ].…”
Section: Insect Antimicrobial Peptidesmentioning
confidence: 99%
“…Porcine alveolar macrophages (PAMs) were obtained from lung lavage samples from the lungs of 3-to 8-week-old PRRSV-negative piglets (37,38) and cultured in RPMI 1640 medium supplemented with 10% heat-inactivated fetal bovine serum (FBS; PAA, Pasching, Austria), 100 U/ml penicillin, and 100 g/ml streptomycin sulfate at 37°C in 5% CO 2 . All animal experiments were approved by the Institutional Animal Care and Use Committee of Sun Yat-sen University.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…et al, 2004). We previously have reported that Cecropin P1 inhibits the replication of PRRSV by blocking its attachment (Guo et al, 2014). In this study, the molecular mechanisms of CD-mediated inhibition against Li11 were characterized during the attachment and the entry stage of virus life cycle.…”
Section: Discussionmentioning
confidence: 97%